RE-IMAGINING THE CONGREGATION’S CALLING – MOVING FROM ISOLATION TO INVOLVEMENT - W.J. Schoeman (Acta Theologica)
Congregations need to re-imagine their calling in their movement from isolation to involvement. Congregations need, from a theological perspective, to answer the question: What is the calling of the congregation? The calling or mission of the congregation provides purpose, direction, and meaning to congregational life. The theoretical understanding lies in a movement in congregational life from isolation towards involvement. The aim is to place congregational life on a continuum, with a limited interaction of the congregation with the environment, on the one hand, and open and engaged interaction of the congregation with the environment, on the other. What is the empirical or contextual position in which congregations find themselves? It is possible to imagine a movement for congregations towards the future. In imagining a movement towards the future, a congregation needs to engage with attitudes and practices that facilitate such a movement.